PENDAMPINGAN KOMPUTERISASI PEMBUKUAN USAHA UKM MENGGUNAKAN APLIKASI AKUNTANSI - Widianingsih, Rini; Sunarmo, Agus; Suparlinah, Irianing; Maghfiroh, Siti (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
Technological development is one of the changes that cannot be It is undeniable that technology and information have influenced the environment rapidly, and this information has become a very important need. Information produced by technology is expected to help individuals or groups as users so that they can carry out their work effectively and efficient. Current technological developments have shown a lot of progress outstanding. By utilizing technology from the community and SMEs can have broad market potential and create a variety of new opportunities profitable. This service is community service that is carried out at UKM Line Production, Bobosan Village. This UKM Line Production is formed by the Bobosan Family Youth Group, whose members are mostly Teenagers drop out of school and drop out of work. Problems faced by SMEs namely after the business organization is formed and business management is still improved using the program manual for bookkeeping. Apart from that, there are other problems is the non-fulfillment of product orders in large quantities due to shortages knowledge about business efficiency and economics. The solution offered on This youth group takes the form of assistance in using bookkeeping Computerization applications in the context of time efficiency and production economics in calculating production costs. This assistance is gradual over 8 months which started from assisting manual bookkeeping repairs until it was held training using computerized applications for SME bookkeeping. The aim of this donation is to help UKM Line Production fulfill their needs product orders by applying the principles of efficiency and economy, time efficiency and economical in calculating production costs for long-term results maximum in order to increase the income of its members. The resulting output from this activity, namely scientific articles published in Junal Ilmiah and presented at the National Seminar and Business Bookkeeping Computerization Applications.